A Matching Problem between the Front Fan and Aft Fan Stages in Adaptive Cycle Engines with Convertible Fan Systems - Xin Meng (Energies, 2021)
In the process of studying the steady-state performance and component matching of adaptive cycle engines with convertible fan system, it was found that the front fan and aft fan stage have a unique matching problem when the mode select valve is closed and engine is operating at higher Mach number conditions. The cause of this matching problem was studied with numeric simulation in this paper. Based on the features of adaptive cycle engines with convertible fan system, the possible methods and their feasibilities of solving this matching problem were also discussed. According to the results, the flow rate adjustment capacity of the aft fan stage directly determines the occurrence and severity of this matching problem. The matching problem can be ameliorated in some extent by either reducing the design second bypass ratio or adjusting the variable geometry mechanisms, but it cannot be completely solved at the aspect of component matching mechanism.